If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(-3) + -5y = 18 Multiply 4 * -3 -12 + -5y = 18 Solving -12 + -5y = 18 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -5y = 18 + 12 Combine like terms: -12 + 12 = 0 0 + -5y = 18 + 12 -5y = 18 + 12 Combine like terms: 18 + 12 = 30 -5y = 30 Divide each side by '-5'. y = -6 Simplifying y = -6
| 4x-7(-x-6)=130 | | 2/5x^2-3=7 | | 4(2x-3)+(2x-3)+x=62 | | -3y-5y=-3-5 | | 9/10y=18 | | -16-4x=-2x+4 | | 8/3x+1/3x=5x+70/3+8/3x | | 5/8p=4.5 | | -58+6x=-4x+72 | | 12g-7g+19= | | 5/8p=41/2 | | 9/10y=2.8 | | 7(3)+y=5 | | 4x+4-4(x+1)=-3+4 | | 1/214+5 | | 2(4x-2)+2x+5=9x+23 | | 1/2b+5b=14 | | 2z-6z=-4 | | 4x=x-6x | | x-14=25+4x | | -14x^2+46x-12=0 | | -6w+8w=19-14 | | 4(7)+7y=28 | | -32+1= | | -3m-3+2=-1 | | 9+7/12=-3 | | 1/6y=-2/5 | | 10.1+0.5p=0.9p+5.3 | | m+3m+8m= | | x+2/3=4/3 | | 7+2x+4=7 | | 26x+26000= |